2003
DOI: 10.1080/13550280390218904
|View full text |Cite
|
Sign up to set email alerts
|

Simian Immunodeficiency Virus Encephalitis in the White Matter and Degeneration of the Cerebral Cortex Occur Independently in Simian Immunodeficiency Virus-Infected Monkey

Abstract: Highly active antiretroviral therapy (HAART) has been successful to reduce progression of acquired immunodeficiency syndrome (AIDS). Nevertheless, recent autopsy analysis of the brain from patients with human immunodeficiency virus (HIV)-1 infection reported same or even increasing numbers of AIDS encephalopathy. This insufficient effect of HAART for central nervous system (CNS) complication might be explained by independent pathogenetic processes in lymph node and CNS. We inoculated macaques with three Simian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 35 publications
4
21
0
Order By: Relevance
“…Six macaques ( #1-6 ) were infected with SHIV -SF162.P4 that was inserted the HIV-related genes, and three macaques ( #7-9 ) were infected with SIV sm543-3 . These two virus strains made rhesus macaques to appear similar brain pathological changes with previous SIVmac239-infected rhesus macaques [10, 2223]. Four macaques ( #10-13) were used as controls.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Six macaques ( #1-6 ) were infected with SHIV -SF162.P4 that was inserted the HIV-related genes, and three macaques ( #7-9 ) were infected with SIV sm543-3 . These two virus strains made rhesus macaques to appear similar brain pathological changes with previous SIVmac239-infected rhesus macaques [10, 2223]. Four macaques ( #10-13) were used as controls.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we used different viral strains that have similar pathological features compared with previous SIVmac239 [10, 2223]. In the SHIV -SF162.P4 and SIV sm543-3 - infected macaques, gliosis was observed in cortical layers II–V using IHC against GFAP (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…136 In vitro studies have also identified a positive correlation between CD4 T-cell depletion and infection by syncytium inducing HIV-1 137,138 or SIV variants. 75,[139][140][141] In addition, multinucleated giant cells, a pathological hallmark of AIDS encephalopathy are also found during SIV-encephalitis 142,143 and these cells revealed DNA fragmentation. 144 The HIV envelope protein has also been reported to cause apoptosis by binding to a chemokine coreceptor.…”
Section: Cell Cycle Dysregulationmentioning
confidence: 99%